Enhancing Students' Narrative Writing Skills through the Circuit Learning Model - Muliana Halawa (PT. Mifandi Mandiri Digital, 2023)
This study aims to improve the narrative writing skills of Grade VII students at MTs Alwashliyah Pantai Labu through the implementation of the Circuit Learning model. The Circuit Learning model is applied as a pedagogical strategy to address the low performance in students’ narrative composition. The research was conducted using a Classroom Action Research (CAR) design consisting of two cycles, each comprising four stages: planning, implementation, observation, and reflection. The participants of this study were 25 seventh-grade students. The findings demonstrate a gradual and significant improvement in students’ ability to write narrative texts. Observational data revealed enhanced teacher guidance and increased student engagement throughout the learning process. Student learning outcomes also showed notable progress, with 60% of students achieving a